Diary of a Wimpy Kid; The Long haul - Kinney,Jeff (Penguin, 2014)
The Heffley family road trip starts off full of promise, then quickly takes several wrong turns--with everything from a fender bender to crazed seagulls--but even the worst road trip can turn into an adventure, and this is one the Heffleys will not soon forget.